HUBUNGAN PAJANAN AMONIA MENURUT DURASI DAN LAMA KERJA TERHADAP KELAINAN FUNGSI PARU PADA PEMULUNG DI TPA SUMUR BATU TAHUN 2023 - Maulyda Shakeela Jasmine (2023)
Lung function disorders can be caused by smoking habits, air pollution, and so on. Sanitary landfills can produce ammonia which can cause lung function disorders. The purpose of this study was to determine the relationship between exposure to ammonia according to duration and length of work to lung function disorders in scavengers at Sumur Batu. The type of research used is analytic observational with quantitative methods and cross-sectional study design. The study was conducted on 85 scavengers selected by purposive sampling from March to May 2023. Data were obtained using a respondent characteristic questionnaire, spirometry, spectrophotometer, and analyzed using the Cox Regression Test. It was found from the study that 54.12% of respondents had pulmonary function abnormalities, 57.14% worked ≥ 9.5 hours/day, and 79.17% had worked for ≥ 8.5 years. Multivariate analysis between lung function disorders with duration and lenght of work found PR 1.116 (95% CI 0.63-1.99) and PR of 3.413 (95% CI 1.51-7.71). There were no confounding variables on the duration of work, whereas for lenght of work, smoking status and history of illness were obtained. There is a relationship between pulmonary function disorders and length of work, after controlling for smoking status and history of lung disease.